The Effect of Manipulation with Different Types of Gloves on Various Mechanical properties and Setting Time of Putty-Type Silicone Impression Materials - Sanam Ayesha, Nauman Ahmed Noor, Aneela Qaisar, Maria Asmat (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate the effects of handling with different type of gloves on the setting time, compressive and tensile strength of putty-type silicone impression materials. Methodology: The study was conducted at COMSATS Lahore and was approved by IRB FMH College of Medicine and Dentistry. In this in-vitro study three different type of gloves (Polythene, Latex and Vinyl) and two different brands each of addition silicone (Flexceed and Elite P&P) and condensation silicone (Zetaplus and Cavex) impression materials were used. These materials were divided into four different groups (A, B, C and D). Each group was subdivided into four sub-groups based on the gloves used for manipulation. Sixty samples(n=20) of two brands each of addition (Elite P&PA, Flexceed B) and condensation silicones (Zetaplus C and Cavex D) were prepared and analyzed to evaluate the setting time, compressive strength and tensile strength of addition and condensation impression materials. The samples were subdivided into groups A1, B1, C1, D1 (Control), A2, B2. C2, D2 (Polythene gloves), A3, B3, C3,D3 (Vinyl gloves) and A4, B4, C4, D4(Latex) respectively. Results: There was a significant effect(p<0.5) on the setting time of Elite P &P when mixed with latex gloves(A4) and Flexceed when mixed with polythene(B2) and latex gloves(B4) There was significant (p<0.5) effect on the setting time of Zetaplus when mixed with vinyl(C3) and latex gloves(C4). There was significant (p<0.5) effect on the setting time of Cavex when mixed with polythene(D2), vinyl(D3) and latex gloves(D4). There was a significant (p<0.5) effect on the tensile strength of both brand of addition and condensation silicone when mixed with polythene, vinyl and latex gloves as compared to control group. There was significant effect on the compressive strength of both brand of addition and condensation silicone except that polythene gloves don’t affect the compressive strength of one group of addition silicon B2(Flexceed) Practical implications: Dental silicone type of impression materials are widely used to fabricate different indirect restorations. Gloves are essential to control cross infection for the safety of the dentist and the patients and cannot be avoided for manipulation of these materials. Worldwide, dentists use different types of gloves to manipulate silicone impression materials. The composition and type of gloves affect the setting time and properties of addition and condensation silicones, and ultimately, it can affect and compromise the clinical outcome too. Conclusion: Latex and polythene gloves should be avoided for the manipulation of addition and condensation silicones putty impression materials due to considerable effect on the setting time. Vinyl gloves are a better choice as all others affected the mechanical properties. Keywords: Addition silicones, Condensation silicones, tensile strength, compressive strength, setting time